(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Vanda spathulata (L.) Spreng. is an important plant of the orchid family of botanical and horticultural importance in the Ayurvedic medicinal system. The Maturase K (matK) gene of plant chloroplast is a strong marker in studying plant molecular systematics, evolution, and genetic polymorphism and is considered as the standard DNA barcode for plants. The gene has an important role in the phylogenetic reconstruction of terrestrial plants. The present study investigated the phylogenetic characterization of matK gene obtained from the plant species Vanda spathulata (L.) through extraction, purification, PCR amplification, and gel elution. The Nucleotide BLAST search revealed similarity with 103 sequences in various closely and distantly related orchid taxa. Mega software and a real-time divergence tree discovered Apostasia odorata has the primitive species for all the sequences including the Vanda spathulata which diverged about 114 million years ago. Limited gene flow was observed among the Vanda and related taxa and the Tajima neutrality test was negative indicating the purifying selection in the matK gene sequence, that evolutionary selection had played a major role rather than the neutral evolution. The species and related other species exhibited higher polymorphism at the nucleotide level. Secondary structure was predicted for the single-stranded matK gene of V. spathulata and the ancestor plant species A. odorata using the Zucker MFold web server and translated through a comparison of ORF with NCBI and BLASTN. The protein was modeled in SWISS MODELLER and compared between the two species. The sequence had high similarity with its ancestor gene sequence and the protein modeled showed complex structure than the ancestor protein as a result of significant evolutionary changes.